1998
DOI: 10.1103/physrevlett.81.2486
|View full text |Cite
|
Sign up to set email alerts
|

Stable and Metastable InGaAs/GaAs Island Shapes and Surfactantlike Suppression of the Wetting Transformation

Abstract: Contrasting behaviors are observed in InGaAs͞GaAs island formation during vapor phase epitaxy: variation of group V partial pressures gives different critical thicknesses for the onset of the StranskiKrastanow transformation, surface coverages, ratios between coherent and incoherent islands, and dissimilar morphologies upon annealing. The latter experiments show that small lens-shaped islands can be found in equilibrium if InGaAs surface energies are minimized, leading to the conclusion that AsH 3 can raise su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 21 publications
1
41
0
1
Order By: Relevance
“…The reason for the size nonuniformity in strained island growth has been discussed elsewhere. 9,10,18 It was also found that small islands in both samples have a square shaped base with rounded corners, as has been observed by atomic force microscopy ͑AFM͒. 19 Cross-section TEM studies showed that, viewed along ͗110͘, islands in both samples have a similar height to basediameter aspect ratio ͑about 1:5͒, irrespective of the size of the islands.…”
mentioning
confidence: 71%
“…The reason for the size nonuniformity in strained island growth has been discussed elsewhere. 9,10,18 It was also found that small islands in both samples have a square shaped base with rounded corners, as has been observed by atomic force microscopy ͑AFM͒. 19 Cross-section TEM studies showed that, viewed along ͗110͘, islands in both samples have a similar height to basediameter aspect ratio ͑about 1:5͒, irrespective of the size of the islands.…”
mentioning
confidence: 71%
“…10 After deposition of GaAs buffer layers at 650°C, the temperature was lowered to 550°C and nanometer sized InGaAs islands were grown by depositing ϳ5 ML of In 0.6 Ga 0.4 As. QW samples were obtained by stopping the growth of InGaAs before the onset of the StranskiKrastanow transformation, giving thin ͑1 nm͒ QWs.…”
mentioning
confidence: 99%
“…6 As under different AsH 3 partial pressures and different growth temperatures. Lower growth temperatures have been identified previously as reducing surface segregation [11,12], but the role of AsH 3 on QD formation has only been speculated [16,17]. Conditions where surface segregation is suppressed and enhanced are identified.…”
Section: Growth Investigations On Ingaas Alloy Saqdmentioning
confidence: 97%